(untitled) - Foster, Kari (Hoboken, N.J., 2007)
Sustainable Residential Interiors takes readers through an integrated design process, showing how sustainable principles and practices can be applied on virtually every level of interior design. Taking a practical, hands-on approach, this accessible and easy-to-understand resource guide includes: Visual examples of sustainable projects and applications; Critical thinking about environmental issues within homes; Guidelines for clients and project teams; Helpful checklists for greening projects and specification; In-depth information to promote understanding and assist in specifying interior finishes and furnishings; Questions for manufacturers and vendors; Effective methods of marketing sustainable design services.
Keywords: Ecological houses,Sustainable engineering,Interior architecture; Design and construction; United States,United States